Transformasi Interaksi Sosial: Dampak Media Sosial terhadap Pola Komunikasi Interpersonal Mahasiswa di Era Digital - Wahyuni, Isti Nursih; Mukhroman, Iman; Kurniawati, Nia Kania (Magister Komunikasi Universitas Sultan Ageng Tirtayasa, 2025)
Students, especially those who constantly use various social media, face major changes in the way they interact with each other due to the rapid growth of digital technology. The purpose of this study is to analyze the impact of social media on interpersonal communication patterns in 2023 batch students of Communication Studies Program, Faculty of Social and Political Sciences, Sultan Ageng Tirtayasa University. Researchers used qualitative analysis by conducting in-depth interviews and direct observation for data collection. This study concludes that social media has a positive impact in expanding communication networks between individuals. Conversely, the utilization of social media can cause a decrease in the value of face-to-face conversations. What is clearly visible is the change in the face of empathy and the depth of interpersonal communication that occurs among students. So, it is important to find the right balance in the use of social media to ensure that the quality of face-to-face social interactions is maintained and not affected by the growing phenomenon of digital communication in the present.